Analisis Tingkat Pelayanan Transportasi Berkesinambungan (Seamless Service) (Studi Kasus: Perjalanan Komuter Jabodetabek melalui Stasiun Kereta Api Bekasi) - Indah, Febriamitha; Susantono, Bambang; Riyanto, Bambang (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
One of the public transportation in Bekasi which serves commuters Jabodetabek is provided by the railroad-based public transport. However, as a satellite city of Jakarta which has more than two million people of population has a massive movement toward Jakarta, Bekasi city transport system is still far from a concept of a seamless services that accomodate the needs of commuters traveling. This research used techniques of qualitative and quantitative method, then though descriptive statistical analysis technique, analytical technique Service Quality (Servual, and Important-erformance Analysis (IPA) which the respondents are passengers of a Jabodetabek Commuters Line. The results suggest that modal choice behavior towards and from the station (Access Mode) as well as from the station to the destination (Egress Mode) is influenced by the ‘Time Value’ and ‘Cost of Transport’. When the modes offered a great time to the station, the more unattractive to the people, as the greater respondent's income make them free to choose the modes, a faster transport time services but requires a greater transport costs.